Cognitive frames of depression and their association with accessibility to mental health communication: a cluster analysis for developing stigma-sensitive targeting strategies - Freytag, Anna; Baumann, Eva; Schindler, Stephanie; Angermeyer, Matthias C.; Schomerus, Georg (Frontiers in Communication, 2024)
Depression is a globally prevalent mental disorder; however, the stigmatization of individuals experiencing depression remains a significant challenge. The effectiveness of mental health promotion efforts and anti-stigma messages is contingent upon individuals' existing beliefs and the stigmatizing potential of their attitudes. Thus, understanding how individuals perceive mental disorders such as depression, as well as their communicative accessibility, is vital from a strategic health communication standpoint. This study explored the prevailing cognitive frames regarding depression in Germany, and the corresponding affective reactions towards individuals experiencing depression. Differences in communicative accessibility, individuals' social proximity to the topic, as well as socioeconomic characteristics were used to inform stigma-sensitive targeting strategies. A representative survey of the German adult population (N = 1,530) was conducted, using a vignette describing a person with symptoms of major depression. Factor and cluster analyses identified four distinct cognitive frames of depression, characterized by varying stigmatizing attitudes and attributions of responsibility. The study has revealed that stigmatizing cognitive frames demonstrate lower receptivity to mental health information. These findings underscore the significance of considering cognitive frames as complex but suitable approaches for target group segmentation in mental health communication strategies. Individuals with stigmatizing perspectives represent a significant portion of the population, have reduced receptivity to mental health information, and are likely to exhibit defensive or even negative affective responses to anti-stigma efforts. Thus, the development of tailored and creative low-threshold strategies fitting well within the cognitive frames of individuals with stigmatizing perspectives is essential.